PCSK9i promoting the transformation of AS plaques into a stable plaque by targeting the miR-186-5p/Wipf2 and miR-375-3p/Pdk1/Yap1 in ApoE−/− mice - Zhao, Yanlong; Liu, Ning; Zhang, Jifeng; Zhao, Lei (Frontiers in Medicine, 2024)
Atherosclerosis (AS) is a complex disorder characterized by disruptions in lipid metabolism, vascular inflammation, and diverse cellular involvement. Recent studies emphasize the role of microRNA (miR) dysregulation in cardiovascular diseases, particularly AS. Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) effectively reduce circulating levels of low-density lipoprotein cholesterol (LDL-C) and lipoprotein(a) [Lp(a)], potentially fostering a more enduring AS plaque phenotype. However, the underlying mechanisms of how PCSK9i enhances plaque stability remain unclear. In this study, ApoE−/− mice were randomly assigned to control, AS, PCSK9i, and Atorvastatin groups. AS was induced through a high-fat diet (HFD), followed by interventions: PCSK9i group received subcutaneous SBC-115076 injections (8 mg/kg, twice weekly), and the Atorvastatin group received daily oral Atorvastatin (10 mg/kg) during the HFD. After interventions, serum analysis, histological assessment (haematoxylin and eosin [H&E], Oil Red O staining), and microarray-centered miRNA analysis using TargetScan and miRTarBase predictions were conducted. Analyses with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) illuminated potential pathways. Real-time fluorescence quantitative PCR (RT-qPCR) quantified target gene expression. The AS group displayed elevated blood lipid levels compared to controls. Both PCSK9i and Atorvastatin effectively attenuated lipid levels, with PCSK9i exhibiting a more pronounced impact, especially on TG and LDL-C. During AS progression, various miRNAs underwent dynamic fluctuations. PCSK9i significantly down-regulated mmu-miR-186-5p, mmu-miR-222, mmu-miR-375-3p, and mmu-miR-494-3p. Enrichment analysis revealed functional associations with cardiovascular smooth muscle cell processes. RT-qPCR showed that PCSK9i significantly upregulated Wipf2, Pdk1, and Yap1 compared to the AS group. Aberrant miRNA expression may play a pivotal role in AS progression in murine models. PCSK9i's subcutaneous administration exerted anti-atherosclerotic effects by targeting the miR-186-5p/Wipf2 and miR-375-3p/Pdk1/Yap1 axes, promoting AS plaque transition into a more stable form.